Quality of Life and Adherence of Diabetic Patients in Different Treatment Regimens - Perwitasari, Dyah A.; Adikusuma, Wirawan; Rikifani, Shoma; Supadmi, Woro; Kaptein, Adrian A. (Indonesian Journal of Clinical Pharmacy, 2014)
The diabetic patientâs quality of life and adherence should be a concerned by health care providers. This study aimed to explore the diabetic patientâs quality of life and medication adherence into account. We recruited 88 subjects in a cross-sectional design. The research subjects were out-patients with type 2 diabetes mellitus in a private hospitals in Yogyakarta City who had taken single or combination of oral anti diabetic and insulin at least six months prior to quality of life measurement. Patients were classified into three groups (monotherapy, oral combination therapy, and oral-insulin combination group). The domains of physical function, energy, satisfaction treatment, and treatment effect were significantly different among the three groups. There were significant associations between treatment satisfaction domain and adherence in monotherapy and oral-insulin combination groups, the health pressure domain and adherence in oral-insulin combination group, the treatment satisfaction domain with adherence in first two groups, and health pressure domain with adherence in oral-insulin combination group. In conclusion, the quality of life of the diabetic patients was good and their medication adherence was at a moderate level.Key words: Adherence, diabetes, Indonesia, quality of lifeÂ Kualitas Hidup dan Kepatuhan Pasien Diabetes Melitus dengan Pengobatan yang BerbedaKualitas hidup dan kepatuhan pasien diabetes melitus (DM) sebaiknya mendapat perhatian dari pemberilayanan kesehatan. Penelitian ini bertujuan untuk mengetahui kualitas hidup pasien DM dan hubungannya dengan kepatuhan pasien. Penelitian ini dilakukan dengan menggunakan rancangan potong lintang. Subjek penelitian ini adalah 88 orang pasien DM tipe 2 di suatu rumah sakit swasta di Yogyakarta yang memperoleh pengobatan baik tunggal maupun kombinasi antara antidiabetes oral dan insulin minimal enam bulan sebelum pengambilan data kualitas hidup. Pasien dikategorikan menjadi tiga kelompok, yaitu kelompok monoterapi, kombinasi oral antidiabetes, dan kombinasi oral-insulin. Terdapat perbedaan yang signifikan antara ketiga kelompok ini pada domain fungsi fisik, energi, kepuasan terhadap terapi, dan efek pengobatan. Terdapat hubungan signifikan antara domain kepuasan pasien dengan kepatuhan pada kelompok monoterapi dan terapi kombinasi oral, domain tekanan kesehatan dengan kepatuhan pada kelompok terapi kombinasi oral-insulin, serta domain kepuasan pasien dan tekanan kesehatan dengan kepatuhan pasien pada ketiga kelompok terapi. Kualitas hidup pasien DM pada penelitian ini cukup bagus dengan kepatuhan pada tingkat moderat.Kata kunci: Diabetes, kepatuhan, kualitas hidup, Indonesia